Innovations in insuring the poor: Microinsurance for health and agricultural risks - Leftley, Richard (International Food Policy Research Institute, 2009)
In 2002 a group of insurance and reinsurance professionals set out to demonstrate that the low-income market was a viable insurance market. The initial aim was to better understand client needs and the willingness of insurers to provide products to this market. The team worked within Opportunity International, which, as a leading microfinance network, was able to provide the borrowers and seed capital needed to get started. Between 2002 and 2005 the team worked as an internal consultancy that designed products around the needs of Opportunity’s clients; designed, discussed, and agreed upon insurance products; and set up a direct bank assurance or “partner–agent” relationship between the bank and insurers. After three years, about 1.5 million borrowers and family members had access to microinsurance—simple insurance products with low benefits and affordable premiums. Although there had been some success in introducing more complex products such as weather index insurance, the majority of clients had access to simple life and property products. It seemed clear to the team that providing access to higher-impact products such as health insurance would require creating a specialized back-office function. In 2006 the team entered discussions with the Bill & Melinda Gates Foundation, which challenged the team to consider how high impact products could be introduced through a range of distribution channels. The main output of the discussion was the creation within Opportunity International of the Micro Insurance Agency. Later, as a result of a US$24.25 million grant, the agency became a separate company, which was renamed MicroEnsure. Central to MicroEnsure’s model is the concept that providing insurance to the poor involves performing three roles: first, carrying the risk; second, acting as the front sales office; and third, carrying out the back-office functions necessary to keep track of who is covered and to ensure a high level of service. During the first three years of the microinsurance effort within Opportunity, it became clear that the weakest part of the link between microfinance institutions (MFIs) and insurers was the back office. Insurers wanted the MFIs to perform the back-office functions, and this approach worked well when the products were simple, such as credit life. When, however, the MFIs had to capture data on spouses and children, introduce a policy that ran for longer than the loan, or administer a significant volume of claims such as those arising from health insurance, the cracks started to appear. In response, the insurance companies took on the back-office functions, and although they were capable, management expenses rose as high as 40 percent, resulting in a higher cost to the client or a reduction in how fast claims were paid out. It seemed that one of the missing components in a functioning microinsurance market was a specialized back-office provider—a void that MicroEnsure set out to fill. The MicroEnsure model uses a range of entities to carry the risk. For life and property insurance, there is an ample supply of local insurance companies in most countries where MicroEnsure works. With more complex products like weather index insurance, MicroEnsure has had to use international reinsurers, such as Swiss Re. To provide health products, MicroEnsure has formed cell captive structures, which are essentially reinsurance pools formed using insurance companies’ capital. Although MicroEnsure does not seek to carry risk on its own balance sheet, it does get heavily involved in designing products on behalf of others. The partnership approach extends to how MicroEnsure reaches out to the poor; by working with a range of front-office partners, it now reaches more than 3.5 million people with a range of life, health, and weather index products. MicroEnsure’s partners include MFIs, child-sponsorship organizations, NGOs, retailers (such as mobile phone companies), and individuals who serve as independent sales representatives (following the Avon business model). With average revenues of US$0.23 per policy, MicroEnsure has no option but to partner with others in order to reach out to the poor. Currently 98 percent of policies are sold to groups. MicroEnsure also plays a key role in training front-office staff and educating clients, using comic books to ensure that people understand the products they are purchasing.